Pemberdayaan Masyarakat dalam Memanfaatkan Limbah Sampah Plastik Melalui Metode Ecobrick di Desa Pamarayan - Tashella Nazha; Munawaroh Munawaroh (Pusat Riset dan Inovasi Nasional, 2025)
Plastic is a non-organic waste that has uses, especially in daily activities. Plastic is widely used by traders to package food and others. The widespread use of plastic by the community and its indiscriminate disposal after use can lead to the accumulation of waste. The problem can be solved with the 3R strategy, namely Reduce, Reuse, and Recycle. Not all locations have facilities to dispose of waste. Nowadays, landfills are a necessity, so it is necessary to provide these facilities. The solution is to make ecobrick products because they can be made easily. This research aims to increase public awareness in Pamarayan Village, Jiput Sub-district, Pandeglang Regency, Banten Province regarding ecobrick products as an invitation to care for the environment in order to create a healthy environment. The method used was the observation method and the approach was training in ecobricking. The result is that the community can understand the importance of maintaining environmental cleanliness and health through proper waste sorting, and are able to make ecobrick products in the form of trash cans from bottle waste for personal or community use.